2013
DOI: 10.1002/adma.201300226
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Exhibits Ideal Physiological Corrosion Behavior for Bioabsorbable Stents

Abstract: Zinc is proposed as an exciting new biomaterial for use in bioabsorbable cardiac stents. Not only is zinc a physiologically relevant metal with behavior that promotes healthy vessels, but it combines the best behaviors of both current bioabsorbable stent materials: iron and magnesium. Shown here is a composite image of zinc degradation in a murine (rat) artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
517
4
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 745 publications
(556 citation statements)
references
References 39 publications
26
517
4
9
Order By: Relevance
“…9,10 Zinc (Zn) was recently suggested as an alternative degradable metal or alloy base. 11,12 The toxicity of zinc is higher than that of iron or magnesium, and concerns have therefore been raised regarding its biocompatibility. Cytotoxicity studies have shown a reduced viability of vascular smooth muscle cells grown in zinc alloy extracts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Zinc (Zn) was recently suggested as an alternative degradable metal or alloy base. 11,12 The toxicity of zinc is higher than that of iron or magnesium, and concerns have therefore been raised regarding its biocompatibility. Cytotoxicity studies have shown a reduced viability of vascular smooth muscle cells grown in zinc alloy extracts.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,16 The corrosion rate of pure zinc appears to be ideal for cardiovascular stent and bone fixation applications in order to retain the mechanical properties during the entire healing process. 11,12 Both in vivo and in vitro studies have determined the corrosion rate to be in the order of tens of micrometers per year, between the degradation rates of magnesium and iron. 11,12,17 Pure zinc, however, is soft and exhibit relatively low tensile strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tests reported recently indicate a good biocompatibility of Zn. 20 In the present work, magnesium, zinc, iron and their alloys are studied with respect to their mechanical and corrosion properties. Appropriate alloying of Mg, Zn and Fe can positively modify their mechanical, corrosion and physical properties, which are important for potential medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the long-term safety of Fe-based stents and the degradation behavior in vivo are still to be evaluated. What is more, zinc has been examined for the first time as a bioabsorbable cardiovascular stent material in 2013 [72]. Although a systemic evaluation of zinc applied in vascular stent needed to be carried out, the early results indicated that zinc was a promising material that could supplant magnesium as the favored base metal from the aspects of biocorrosion rate and corrosion products in vivo.…”
Section: Biodegradable Stentsmentioning
confidence: 99%